STRATEGI PENGEMBANGAN BAWANG MERAH DI KOTA PEKANBARU - Afrizal; Syaiful Hadi; Evy Maharani (UIR Press, 2018)
ABSTRACT One of the efforts to reduce dependence on imported shallots is by improving the production of shallots. The purpose of this research is to making formulate a strategy for developing lowland shallots agribusiness in the city of Pekanbaru. The research is held in 2018 with responded to the farmer of shallots as many as 24 people and 3 field extension officers. The analysis A’WOT is the combination of SWOT and AHP is used to formulate the strategy for developing shallots in the city of Pekanbaru. The results show that the average of net income to the farmer's bima Brebes varieties with a land area of 0,5 ha is Rp. 47.187.000. The RCR value of shallot farming is 1,50 which means that the Brebes variety of shallot farming in Pekanbaru City is economically profitable to it can continue. The result of the analysis of A’WOT shows that 10 strategies can be implemented in the development of shallots agribusiness in Pekanbaru with priority strategy development of shallots agribusiness in the city of Pekanbaru is shallots agribusiness. Keywords: Shallots, agribusiness, SWOT, AHP